The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2008
DOI: 10.1007/s10562-008-9784-y
|View full text |Cite
|
Sign up to set email alerts
|

Production of Middle Distillate Through Hydrocracking of Paraffin Wax over NiMo/SiO2–Al2O3 Catalysts: Effect of SiO2–Al2O3 Composition on Acid Property and Catalytic Performance of NiMo/SiO2–Al2O3 Catalysts

Abstract: SiO 2 -Al 2 O 3 supports with different composition were prepared by a precipitation method in order to control the acid property of SiO 2 -Al 2 O 3 supports. NiMo/ SiO 2 -Al 2 O 3 catalysts were then prepared by an impregnation method and sulfided for use in the production of middle distillate through hydrocracking of paraffin wax. It was revealed that MoS 2 phase was dominantly formed in the NiMo/SiO 2 -Al 2 O 3 catalysts, while Ni-Mo-S phase was not detected due to its fine dispersion. Acidity of NiMo/SiO 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 23 publications
2
11
0
Order By: Relevance
“…The correlation clearly shows that conversion of paraffin wax and selectivity for middle distillate are closely related to the acidity of the catalyst. Conversion of paraffin wax increased with increasing acidity of the catalyst, in good agreement with the previous work [27]. On the other hand, selectivity for middle distillate decreased with increasing acidity of the catalyst.…”
Section: Effect Of Sio 2 Content On the Catalytic Performancesupporting
confidence: 92%
“…The correlation clearly shows that conversion of paraffin wax and selectivity for middle distillate are closely related to the acidity of the catalyst. Conversion of paraffin wax increased with increasing acidity of the catalyst, in good agreement with the previous work [27]. On the other hand, selectivity for middle distillate decreased with increasing acidity of the catalyst.…”
Section: Effect Of Sio 2 Content On the Catalytic Performancesupporting
confidence: 92%
“…As shown in Fig. 4(a), conversion of paraffin wax increased with increasing acidity of the catalyst, in good agreement with the previous work [40]. It is believed that large acidity of the catalyst enhanced the cracking activity of the catalyst, leading to an increase of conversion of paraffin wax.…”
Section: Effect Of Acid Property On the Catalytic Performancesupporting
confidence: 90%
“…These tendencies for Y zeolite-containing catalysts were much larger than those for b zeolite-containing catalysts probably because b zeolite itself has the higher activity for paraffin cracking and the effect of the addition of matrix on the catalytic cracking performance of b zeolite-containing catalysts is lower than that for Y zeolite-containing catalysts. Some reports pointed out that the increase in aluminum content brought about the increase in the catalytic activity [4,34,[36][37][38][39][40][41] and the hydrogen transfer [4,37,41]. It was reported that the diffusion of aluminum into silica skeletal would generate the BrØnsted acid site to increase the activity because the activity increased with increasing calcination temperature of silicaalumina [34].…”
Section: 2mentioning
confidence: 99%